Foiled - Yolen, Jane.; Cavallaro, Michael, 1969- (New York ; London : First Second, 2010)
Aliera is a star at fencing, but at school no one notices her--until her new lab partner Avery begins flirting with her. Aliera's mother just bought her a foil from a garage sale, and it has a strange jewel attached to the hilt. Will Aliera's first date be ruined when magical creatures try to steal her foil?
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Fencing -- Comic books, strips, etc; Supernatural -- Comic books, strips, etc; New York (N.Y.) -- Comic books, strips, etc; Fencing -- Fiction; Supernatural -- Fiction; New York (N.Y.) -- Fiction; Fantasy comic books, strips, etc; Young adult fiction